Guidelines and quality measures for the diagnosis of optic ataxia - Borchers, Svenja; Müller, Laura; Synofzik, Matthis; Himmelbach, Marc (Frontiers in Human Neuroscience, 2013)
Since the first description of a systematic mis-reaching by Bálint in 1909, a reasonable number of patients showing a similar phenomenology, later termed optic ataxia (OA), has been described. However, there is surprising inconsistency regarding the behavioral measures that are used to detect OA in experimental and clinical reports, if the respective measures are reported at all. A typical screening method, that was presumably used by most researchers and clinicians, reaching for a target object in the peripheral visual space, has never been evaluated. We developed a set of instructions and evaluation criteria for the scoring of a semi-standardized version of this reaching task. We tested 36 healthy participants, a group of 52 acute and chronic stroke patients, and 24 patients suffering from cerebellar ataxia. We found a high interrater reliability and a moderate test-retest reliability comparable to other clinical instruments in the stroke sample. The calculation of cut-off thresholds based on healthy control and cerebellar patient data showed an unexpected high number of false positives in these samples due to individual outliers that made a considerable number of errors in peripheral reaching. This study provides first empirical data from large control and patient groups for a screening procedure that seems to be widely used but rarely explicity reported and prepares the grounds for its use as a standard tool for the description of patients who are included in single case or group studies addressing optic ataxia similar to the use of neglect, extinction, or apraxia screening tools.